Effects of resistance training with blood flow restriction on explosive power of lower limbs: a systematic review and meta-analysis - Wang, X.; Qin, X.; Ji, S.; Dong, D. (Journal of Human Kinetics, 2023)
The purpose of this systematic review and meta-analysis was to compare changes in explosive power between blood flow restriction training and traditional resistance training protocols. Searches of PubMed, Scopus, Web of Science, and OVID Medline were conducted for studies. Inclusion criteria were: (a) healthy people; (b) randomized controlled or controlled trials; (c) outcome measures of explosive performance (peak power, rate of force development, jump performance, sprint performance, etc.); (d) involving a comparison between blood flow restriction training and traditional resistance training. Quality assessment was conducted using the Physiotherapy Evidence Database (PEDro) scale. A total of 12 studies (262 subjects) were finally included for analysis. The PEDro scale score had a median of 5 of 10 points (range: 3-6 points). Significant small to moderate improvements were observed in blood flow restriction training [jump: standard mean difference (SMD) of 0.36 (95% CI: 0.02; 0.69); sprint: SMD of 0.54 (95% CI: 0.00; 1.07); power: SMD of 0.72 (95% CI: 0.17; 1.27)] when compared to traditional resistance training. The findings indicate that blood flow restriction training is more effective in improving explosive power of lower limbs compared to traditional resistance training in healthy people. In addition, blood flow restriction with a wide cuff (? 10 cm) during training improved explosive power better than with a narrow cuff or during the rest interval. Blood flow restriction training is very suitable for athletes in short competitive seasons and those who are not able to tolerate high loads (i.e., rehabilitators and the elderly)